Self-evaluation: aviation fire and rescue study program in improving quality - Abdullah, Anton; Hamzah, Syukri; Winarto, Hadi (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
This research was conducted as a first step in improving the quality of the Aviation Fire and Rescue Study Program of Palembang Aviation Polytechnic in evaluating itself to obtain information and recommendations for descriptions of each assessment criteria that need to be considered to determine the feasibility of the Study Program based on the criteria that refer to the National Higher Education Standards. This study uses a qualitative approach with a descriptive method, in which the researcher explores the criteria of the Aviation Fire and Rescue Study Program of the Palembang Aviation Polytechnic then looks at suggestions and recommendations to see whether these conditions or criteria have met the Study Program Accreditation based on criteria that refer to the National Standard. Higher education. The results showed that the Aviation Fire and Rescue Study Program of Palembang Aviation Polytechnic got a score of 246.72. The description of the assessment based on the data and information of the Aviation Fire and Rescue Study Program of Palembang Aviation Polytechnic reaches the Good criteria, it needs more effort that must be improved and get attention to be able to go to the Very Good criteria and towards Excellence.